Pemberdayaan Ekonomi Masyarakat Melalui Revitalisasi Unit Pengelola Keuangan (UPK) Kelurahan Cicurug - Wulan Riyadi; Latief Z.Nur; Nita Hernita; Melia Wida Rahmayani; Eli Achmad Mahiri (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this PKM is to provide understanding and knowledge about productive UPK management, based on the phenomenon that occurred at UPK Cicurug Village in Majalengka Regency, West Java, namely regarding strategies for handling problem loans through credit analysis training and strengthening organizational governance through organizational training, as well as encouraging the creation of good governance manage UPKs that are competitive in accordance with the nature of their presence, namely to improve the economic welfare of the village community. The PKM method used is by providing training related to financial management and credit analysis. It is hoped that this PKM activity will provide UPK members with an understanding in the field of financial management that can increase and a change in mindset for the community and UPK managers to be more professional and able to run the UPK organization well through community economic empowerment programs.